SPELLONYMS IN MODERN ENGLISH FAIRY TALES AND THEIR ROLE IN DEFINING THE GENRE OF THE WORK - Odilova Nozima Nizomiddinovna (Bright Mind Publishing, 2025)
Spellonyms have aesthetic, ideological, and symbolic purposes in contemporary English fairy tales, and they also aid in defining the genre's traits. Through them, the work's genre is more clearly expressed, its spiritual notion is strengthened, and its content and significance are expanded. As a result, studying magical characters helps one comprehend the structure, genre affiliation, and semantic levels of a literary work better. Spellonyms are crucial for determining a text's genre.
Keywords: Magical characters, spiritual notions, spellonyms.